The Mongols in Iran - Lane, George, author.
1 online resource
Keywords: "This is an annotated, paraphrased translation of a thirteenth century historical chronicle penned, though not necessarily authored, by a widely respected Persian scholar of the Iranian Ilkhanate (1258-1335), Qu?b al-D?n Sh?r?z? (d.1311)."--Provided by publisher.